Broadening the Categories of Patients Eligible for Extended Venous Thromboembolism Treatment - Schindewolf, Marc; Weitz, Jeffrey Ian (Thrombosis and Haemostasis, 2020)
Traditionally, venous thromboembolism (VTE) resulting from major transient risk factors (e.g., surgery or trauma) or a major persistent risk factor such as cancer, has been defined as being provoked, whereas unprovoked VTE encompasses events without an identifiable cause. These categorizations influence anticoagulant treatment duration; unlike VTE provoked by major transient risk factors, extended anticoagulation beyond 3 months is advised for patients with cancer or unprovoked VTE due to risk persistence after treatment cessation. However, some patients with VTE provoked by minor transient or minor persistent risk factors may also be candidates for extended anticoagulation therapy due to the continuing risk of recurrence. In patients who require extended therapy, vitamin K antagonists (VKAs) are effective but are associated with an increased risk of bleeding and various treatment burdens (e.g., anticoagulation monitoring and dose adjustment). Evaluations of extended VTE treatment with the less-burdensome direct oral anticoagulants such as apixaban, dabigatran, edoxaban, and rivaroxaban show that they are at least as safe and effective as VKAs in a broad range of patients. In addition, apixaban and rivaroxaban offer more than one dosing option, allowing tailoring of treatment to the patient's specific risk factor profile. Analysis of more granular definitions for risk factor groupings has also yielded vital information on the most appropriate strategies for the treatment of patients with specific risk factors, highlighting that extended anticoagulation treatment may benefit those with minor transient and persistent environmental and nonenvironmental risk factors who commonly receive shorter-duration therapy.
Keywords: anticoagulants; body weight; frail elderly; renal insufficiency; venous thromboembolism